Informal Resistance on a Dominican Sugar Plantation During the Trujillo Dictatorship - Legrand, Catherine C. (Universidad Autónoma de Santo Domingo (UASD), 1996)
The cane cutters who toiled on the great foreign-owne sugar plantations of the twentieth-century Caribbean were sorne of the most exploited of Latin American wage workers. Employed only for the five-month sugar harvest, they did long hours of back-breaking work in stifling heat for barely subsistence pay. Because the work was seasonal and many of the workers were temporary migrant laborers from other countries, unionization was difficult and legal protection minimal.